Microglial translational profiling reveals a convergent APOE pathway from aging, amyloid, and tau - Kang, Silvia S.; Ebbert, Mark T.W.; Baker, Kelsey E.; Cook, Casey; Wang, Xuewei; Sens, Jonathon P.; Kocher, Jeanne-Pierre; Petrucelli, Leonard; Fryer, John D. (The Journal of experimental medicine, 2018)
Alzheimer’s disease (AD) is an age-associated neurodegenerative disease characterized by amyloidosis, tauopathy, and activation of microglia, the brain resident innate immune cells. We show that a RiboTag translational profiling approach can bypass biases due to cellular enrichment/cell sorting. Using this approach in models of amyloidosis, tauopathy, and aging, we revealed a common set of alterations and identified a central APOE-driven network that converged on CCL3 and CCL4 across all conditions. Notably, aged females demonstrated a significant exacerbation of many of these shared transcripts in this APOE network, revealing a potential mechanism for increased AD susceptibility in females. This study has broad implications for microglial transcriptomic approaches and provides new insights into microglial pathways associated with different pathological aspects of aging and AD.